STING Agonists in Head and Neck Squamous Cell Carcinoma. Issue 5 (September 2022) - Wallington, David G.; Contessa, Joseph N.; Hayman, Thomas J.
Abstract: Despite the development of new treatment paradigms and improved biologic understanding of head and neck squamous cell carcinoma (HNSCC), therapeutic resistance remains a substantial problem, and novel treatment approaches are needed. Stimulator of interferon genes (STING) is a critical regulator of the antitumor response through regulation of both immune-dependent and tumor-intrinsic mechanisms. As such, the STING pathway has emerged as a rational pharmacologic target leading to the development of multiple STING agonists. These compounds have impressive preclinical efficacy as single agents and with PD-1 (programmed death-1) axis agents. However, clinical evaluation in this context has yet to show substantial efficacy. In contrast to monotherapy approaches, activation of STING in combination with DNA-damaging agents has been shown to enhance the effect of these agents in preclinical models and represents a promising approach to improve outcomes in patients with HNSCC. In this review, we will discuss the preclinical and clinical data supporting the use of STING agonists and highlight potential avenues of exploration to unlock the potential of these agents in HNSCC.